El tiempo de retención hidráulico de un lecho bacteriano aerobio relleno con caña guadua y la nitrificación en un residual sintético - Cedeño Sánchez, Irene Nathaly (2016)
This research aimed to study the hydraulic retention time (HRT) in a bacterial bed aerobic (LBA) stuffed with bamboo cane in the treatment of synthetic wastewater (ARS), in which eight treatments of variation of HRT is offered for to know the best efficiency of nitrification. synthetic wastewater due to the inconvenience and danger involved in handling real industrial wastewater was produced, hypothesis testing was performed to demonstrate the significance about the validity of the low variability as to the concentrations of each parameter using the distribution of the "Student's t" resulting in 99, 5% under laboratory analyzes both BOD5 and total nitrogen. The implementation for each of the eight levels to study which lasted 13 days were incubation period and to take the sample in the settler, then proceeded to change the flow. With the test results obtained in the laboratory the best fit curve was used with the Statgraphics program, where it was shown that the best efficiency of the LBA is increased hydraulic retention time between 0,76 and 1,53 d because there more efficient nitrification, ranging between 86 and 89%, for total nitrogen elimination.